The Biochemical and Kidney Histopathological Parameters in Hyperoxaluria Rats Treated with Breadfruit Leaf Extract - Susilo, Jatmiko; Purnama, Siswanta Jaka; Wahyuni, Ardianti; Purwanto, Bambang; Doewes, Muchsin; Indarto, Dono (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: This study was to analyze the administration of breadfruti leaf extract to changes in biochemical parameters and renal histology in hyperoxaluria rats.Methodology: The experimental study used 6 groups, each of 5 mice that are EG, Normal, Vitamin E, an ethanol extract of breadfruit 100, 200 and 400 mg/kg BW. Blood data for the analysis of biochemical parameters and kidney were taken at the end of the experiment for histological analysis of kidney changes. Results: Research shows that the purified ethanol extract of breadfruit leaf can prevent increases in MDA levels, reduce creatinine and BUN levels, increase body weight, prevent hypertrophy and kidney damage Conclusion: Purified ethanol extract of AA leaves has an antioxidant, nephroprotective activity, protect kidney inflammation, and kidney damage in nephrolithiasis rats and the effective dose is 400 mg/kg BW. The higher the extract dose, the more effective to reduce the biochemical and histopathological parameters in hyperoxaluria rats.Applications/Originality/Value: as a basis for futher studies of molecular biology in the prevention of kidney disorder.